(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2010)
The list of Bryophytes of the reserve is given in the article whith 46 species, including 3 from division Marchantiophyta and 43 – Bryophyta. Pottiaceae family has the greatest number of species – 9, Brachytheciaceae – 6, Bryaceae – 6, Hypnaceae – 5. The Bryum genera dominates with 6 species here. The genera Orthotrichum and Brachythecium have 3 species lach, 9 genera are represented by 2 species, the rest genera have only one species in each.